The Mosque as a Community Center: A Concept and Evolution - Omer, Spahic (AS Noordeen, 2014)
It is a fact that the Muslims of today are subjected to trials rarely paralleled in history. At the same time, however, as another undeniable fact, there are more than a few serious attempts and initiatives aimed at remedying and improving the situation. Calling for the revival of the status of the mosque institution as a community center is integral to a majority of such constructive attempts and initiatives. Thus, studying meticulously and critically the roles and functions of the mosque in history when Muslims and the Islamic state through their recurring ups and downs dominated the world scene, will always be vital. Numerous lessons can be derived from such an undertaking, as history which progresses in what could be described as a cyclic rather than horizontal pattern, often repeats itself. The lessons thus obtained will be very significant in that the mosque institution and the world of its diverse social roles and functions always epitomized the message of Islam and the civilizational triumphs, or slumps, of Muslims. Indeed, no Muslim revival is completely possible today without mastering the history of Islam and Muslims, on the one hand, and without mastering the history of the mosque institution and how its intrinsically true and deserving standing and roles in society can be restored, on the other. Studying and reviving the mosque today cannot be done in a vacuum and in isolation from the sway of both history and the pressing current needs of Muslims. Moreover, the truth is only one, and so is Allah, its source. The origins, meaning and purpose of life with all of its units, including human beings, furthermore, are also one and the same, reverberating the disposition of the heavenly paradigm from which it emanates. Hence, the mosque institution too, which symbolizes most powerfully the dynamic presence of the truth and its forces, and its relentless confrontation for supremacy with the falsehood and evil and the forces of their own, is as old as the truth itself and its protagonists. In other words, from the down of the human presence on the face of the earth, mosques had to feature prominently thereon. This was so because the truth and its people are always the cause and the mosque phenomenon is an effect. The two are indissoluble. So strong is the relationship between them that they are destined to rise and fall together. Truly, if separated from each other, neither the truth with its devotees, nor the mosque can exist or survive on its own. They depend on, and draw their respective ethos and strengths, from each other. Once activated and made fully operational, mosques have the potential to be turned into their communities’ guardians, the driving force and the heartbeat behind their progress. Mosques in their capacities as the houses of Allah (buyut Allah) can become unrivaled community development centers. If neglected, however, Muslims will never be able to conjure an equivalent alternative to mosques, as the recent history of the Muslim world especially has shown. Having said this, it stands to reason, there will never be a Muslim community which will not experience a positive change if they change constructively the status and functions of their mosques, i.e., if they constructively change themselves and their relationships with their mosques, their lives’ focal point. Similarly, there will never be a Muslim community which will not experience a detrimental change if they change negatively the status and functions of their mosques, i.e., if they negatively change themselves and their relationships with their mosques. Based on this strong and reciprocal relationship between mosques and Muslims, mosques are the mirrors of their communities’ devotion to Islam and its cause. So, for a person to study a community’s spiritual, cultural and civilizational major accomplishments, it will suffice for him to study the performances of that community’s mosques only. In the same vein, studying a truly purposeful and serviceable mosque will offer without ambiguity an answer to a question “what is Islam?” because the mosque in Islam demonstrates on a practical plane what Islam on a theoretical plane denotes. Form the moment the Muslim city-state of Madinah was created, with the Prophet (pbuh) at its helm, the mosque played the role of a community development center. It typified everything Islam and Muslims stood for. However, many aspects of the mosque’s position and role were changing with changes necessitated by the time-space factors and with changes in the conditions of Muslims - albeit with the purpose and essence of the mosque institution forever remaining the same. Observing this balance between the permanent and temporary, and between the normative and fluctuating, concerning the mosque institution is crucial for optimizing the roles and functions of mosques. After the Prophet (pbuh), the Islamic state grew and expanded rapidly. Madinah remained the capital city until the second part of the rule of Ali b. Abi Talib, the fourth rightly guided caliph, when the capital was moved to Kufah in Iraq. After Ali, when Mu’awiyah b. Abi Sufyan assumed the power in 41 AH / 661 AC, establishing in the process the Umayyad dynasty, the capital of the Islamic state was transferred to Damascus in Syria, the seat of the Umayyad dynasty. Following the ousting of the Umayyads from power by the Abbasids in 132 AH / 750 AC, the capital of the state was also moved to some low profile towns in Iraq, the center of the Abbasid rule. This was until the city of Baghdad was established in 145 AH / 762 AC. By the time the city of Samarra in Iraq was established in 222 AH / 836 AC by the Abbasid caliph al-Mu’tasim, who acted on expediency rather than principles in order to replace Baghdad as the state capital, the Islamic state was going through a critical period which marked the end of a powerful and effective centralized government and with it the virtual end of the reasonably unified and resilient Muslim community. What ensued thereafter was the formation of a number of independent and semi-independent states and quasi-states whose recurring warring tendencies and disputes at times were due to the people’s vast differences as regards some fundamental ideological and religious substance of Islam. This, in turn, spawned a sizeable measure of disunity, schism, conflicts, spiritual laxity and general decline in Muslims and their civilizational initiative. Without doubt, the present state of affairs of Muslims and their community owes much to what was transpiring in the past, both near and distant, at all the levels of Islam’s and Muslim reality. The mosque institution, the center and symbol of Islam and the Islamic community since its inception, was not immune to those rapid and sweeping changes. At times, the mosque was victimized too. It was attempted to be manipulated for some improper goals. At times, moreover, the mosque tried to transcend the current predicaments and just stay neutral. Yet, at some other times, it played the active roles of a reformer. It was an agent of positive change. Its roles were proactive rather than reactive to its surrounding volatile milieu. Surely, the present state of affairs of the mosque institution in the Muslim world owes much to what was transpiring in the past, both close and remote, at all the levels of the mosque’s existence. While thoroughly studying the history of Islam and Muslims, in general, and the history of the mosque phenomenon which exemplifies the former, in particular, as part of a comprehensive revivalist and Islamization project and plan, Muslims must remember an underlying rule which both the Holy Qur’an and history clearly and repeatedly bring to light. That rule is: in order for one to know and diagnose one’s present state, one must know his past; and for one to be able to chart his future course, one must know both his past and present conditions. This applies to the fates of societies more than anything else. Indeed, any other approach is a flawed and misleading one. It denotes one of the plainest paradoxes that one can adopt. It is a self-deception and self-hypocrisy. The disposition of a present condition, in a person or a society, owes much to the past conditions that preceded it. Also, the disposition of future conditions will always owe much to both the present and past ones and how people handled them. People who are ignorant about, and indifferent towards, their history are people with a fake identity. They possess no real life orientation and mission, and they regularly waver in some of the most important things in life. Their civilizational undertakings, at best, are shortsighted, myopic and superficial, often serving not their own interests, but the interests of those parties and groups to the rhythm of whose political or economic currents they swing. This situation is similar to a seriously sick person who went to see a doctor. Indeed, the only way for the person’s illness to be properly and quickly cured is that he informs the doctor about what had transpired earlier: what he had eaten, or what unusual he had done or had happened to him, for example. The doctor will ask if the person had similar, or some other serious, illnesses in the past and how he handled them. He will ask, furthermore, whether the person is allergic to certain medications. Knowing the medical history of the person’s immediate family members will also be crucial to the doctor. Only when the doctor is well acquainted with all these matters, he will be able to correctly diagnose the illness and proceed with an effective and beneficial therapy for the ill person. Any failure in properly diagnosing the person, either due to the doctor’s ignorance of the person’s present and past conditions, or due to some misleading information given to the doctor, will inevitably lead to a failure in curing the person from his decease. As a result of this failure, sometimes a wrong therapy may lead not only to the prolonged suffering of a patient, but also to deterioration in his condition. It may even lead to his death. It is because of all these extremely important factors that writing this book has been undertaken. The book is divided into three chapters, echoing and tackling, to a great extent, the issues and problems raised above. The chapters are entitled as follows: “Islam and the Indispensability of Mosques”, “The Prophet’s Mosque as a Community Center”, and “The Mosque as a Community Center after Prophet Muhammad (pbuh)”. In the first chapter, the following issues, mainly, were thoroughly discussed: the meaning of life and worship in Islam; the meaning of the concept of the mosque; the hierarchy of mosques: from small private domestic mosques to the universe as a mega mosque or a place of worship; the mosques before Prophet Muhammad (pbuh) focusing on the first two mosques which were built on the earth: al-Masjid al-Haram and al-Masjid al-Aqsa. In the second chapter, the following themes, principally, were dwelled on: Prophet Muhammad (pbuh) and the mosques institution; the mosque as a catalyst for social transformation in Madinah; the Prophet’s mosque in Madinah and its manifold religious, socio-political, educational and welfare roles and functions; a comprehensive code of conduct for establishing and using mosques before and today. In the third and largest chapter, the following topics, chiefly, were extensively dealt with: the evolution of the mosque institution after the Prophet (pbuh); the full institutionalization of the mosque’s roles and functions; the institutional decentralization in the Islamic state; the influence of the mosque on the medieval Muslim theorizing on urban planning and development; the relationships between the mosque institution and other social institutions following the institutional decentralization; the meaning and significance of the institutional ideological harmony between the mosque institution and other social institutions; the relationship between the performances of the mosque and the rift between the scholars (ulama’) and the rulers (hukkam); the relationship between the performances of the mosque and the emergence of funerary institutions. The book seeks to enhance the awareness of all the relevant parties, from the people on the street to the government and its agencies, as to the importance of correctly conceptualizing, establishing and using the phenomenon of the mosque institution as a community center, employing some of the most decisive episodes of the Muslim history as inspiration and guidance. Though very much history oriented, the book contents were dealt with topically or thematically, rather than chronologically. The principal objectives of the book are: 1) To critically examine the position, roles and functions of the mosque institution as a community center in Muslim history, focusing on some of the most relevant periods of the Muslim history and on some of the most important Muslim geographical regions. 2) To provide a blueprint for restoring the intrinsic status and roles of the mosque institution as a community center today. 3) To clarify and remove some pervasive misconceptions and misunderstandings about the Islamic society in general and the subject of the mosque institution in particular.